1994
DOI: 10.1002/zaac.19946200107
|View full text |Cite
|
Sign up to set email alerts
|

Erste Kristallstruktur eines Selenans; Metall(II)‐Komplexe mit dem 2,4,6‐Tris(trifluormethyl)selenophenolat‐Liganden

Abstract: RfSeH 1 entsteht in einer Eintopfsynthese bei der Reaktion von RfLi [Rf = 2,4,6‐Tris(trifluormethyl)phenyl] mit elementarem Selen und anschließender Umsetzung mit HBF4. Mit 1 konnte zum ersten Mal die Kristallstruktur eines Selenans bestimmt werden. Bei der Umsetzung von 1 mit M[N(SiMe3)2]2 (M = Zn, Pb) im Molverhältnis 2:1 erhält man die Metallselenophenolate Zn(SeRf)2 · HN(SiMe3)2 2 und [Pb(SeRf)2]2 3. 2 kristallisiert als Hexamethyldisilazan‐Addukt, während 3 als Dimer vorliegt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 25 publications
(4 reference statements)
0
16
0
Order By: Relevance
“…There are two derivatives of the general formula [Pb 2 M 3 ]' 2 , where Μ is a chalcogen, Se [160] orTe [161], and these are isostructural ( [82,85,102,[162][163][164][165][166], or two N-donor ligands [167], two S-donor ligands [168][169][170][171], two P-donor ligands [172,173] or two Se-donor ligands [174], Distorted edge-shared trigonal [167][168][169][172][173][174], tetrahedra [102,162,163,166], trigonal bipyramidal [85]. pseudo-octahedral [164,165] and heptahedral [82,170,171] are observed.…”
Section: Lead(ll) Compoundsmentioning
confidence: 99%
“…There are two derivatives of the general formula [Pb 2 M 3 ]' 2 , where Μ is a chalcogen, Se [160] orTe [161], and these are isostructural ( [82,85,102,[162][163][164][165][166], or two N-donor ligands [167], two S-donor ligands [168][169][170][171], two P-donor ligands [172,173] or two Se-donor ligands [174], Distorted edge-shared trigonal [167][168][169][172][173][174], tetrahedra [102,162,163,166], trigonal bipyramidal [85]. pseudo-octahedral [164,165] and heptahedral [82,170,171] are observed.…”
Section: Lead(ll) Compoundsmentioning
confidence: 99%
“…Initial experiments indicate however, that the diarylgermylene (Rr)2Ge might be isolable. in high yields [22]. At room temperature (Rr)2Ge seems to be thermally labile and further experiments are necessary in order to elucidate the chemical nature and reactivity pf this diarylgermylene [20].…”
Section: B) Germanium Derivativesmentioning
confidence: 99%
“…The bright yellow color is virtually unchanged between -196 "C and the melting point. According to a recent X-ray structure determination it is dimeric in the solid state and thus has to be formulated as [(RFSe)2Pb]2 [22]. A single crystal X-ray structure analysis revealed that (RF)2Pb is monomeric in the solid state (Fig.…”
Section: D) Lead Derivativesmentioning
confidence: 99%
“…17, 18 Both compounds are chalcogenolates of divalent lead with an electron sextett and a resulting electron deficiency. Due to the steric bulk of the substituents they are nevertheless monomeric molecules which are sublimable 17 and show a good stability in polar organic solvents.…”
Section: General Aspectsmentioning
confidence: 99%
“…Preparation of 2,4,6-tris(trifluoromethyl)selenophenol 17 In a 100 mL-Schlenk flask 5.00 g (17.7 mmol) of 2,4,6tris(trifluoromethyl)benzene were dissolved in 27 mL of diethylether and cooled to -78 • C. 11.1 mL of butyllithium (1.6 M in hexane, 17.7 mmol) were added dropwise and it was stirred for 30 min while the solution was allowed to warm to room temperature. A slight excess of selenium (1.68 g, 21 mmol) was added and stirring was continued for 6 h. Subsequently tetrafluoroboric acid in diethylether (17.7 mmol HBF 4 ) was syringed into the reaction mixture and stirring was continued overnight under exclusion of light.…”
Section: Preparation Of Tris(trimethylsilyl)silyltellurolmentioning
confidence: 99%